Exploration of Chinese and Finnish Kindergarten Teachers’ Perceptions of Their Professional Competence in Early Childhood Education - Yang, Wenwen (fi=Turun yliopisto|en=University of Turku|, 2016)
This study investigated Finnish and Chinese kindergarten teachers’ own perceptions of their professional competences in early childhood education. Here, competence includes teachers’ theoretical and practical professional competences in the following four domains: child growth and development, families and colleagues, pedagogy and education, and professional development. Face-to-face interview or online interviews and online interviews were conducted to collect data. Altogether 16 participants participated in the study, including eight Chinese kindergarten teachers and eight Finnish kindergarten teachers. The results indicated that both Chinese and Finnish teachers experience problems in applying theory to practice, although Finnish teachers tend to have a more solid theoretical basis. Finnish teachers focus more on children’s interests and needs and have more autonomy in education, whereas, Chinese teachers emphasize on the improvement of teaching strategies. Chinese teachers believe in the idea of child-centered teaching and play-based learning, but still within the collectivist context. It is also seen hard to be implemented in practice. Chinese and Finnish teachers all report a pleasant relationship with children and harmonious collaboration with parents and colleagues. However, their self-evaluation skills are not high. It is thus suggested that different forms of self-evaluation methods are adopted on a regular basis to improve kindergarten teachers’ self-assessment skills.